The Queens separation problem - Chatham, R. Douglas; Fricke, Gerd H.; Skaggs, R. Duane (Utilitas Mathematica, 2006)
We define a legal placement of Queens to be any placement in which any two attacking Queens can be separated by a Pawn. The Queens separation number is defined to be equal to the minimum number of Pawns which can separate some legal placement of m Queens on an order n chess board. We prove that n + 1 Queens can be separated by 1 Pawn and conjecture that n + k Queens can be separated by k Pawns for large enough n. We also provide some results on the separation number of other chess pieces.